Readiness of year 1 students to learn science process skills in english : A Malaysian experience - Sulaiman, Tajularipin; Hassan, Aminuddin; Baki, Roselan (International Journal of Instruction, 2009)
The Malaysian Ministry of Education has implemented the use of English as the medium of instruction at primary school level beginning 2003. These students are the main group of people affected by this change in policy. Besides, the implementation of the approach also raises the readiness of students in the rural areas. Therefore, the aims of the study are a) comparing between year 1 students from the urban and the rural areas in terms of their competency of science process skills which use English terminologies, and b) determining the level of readiness of year 1 students in learning the science process skills in English for Science subject. The study adopted a quantitative research method design to make a comparison between Year 1 students in the rural and urban areas and to determine the level of readiness. The research findings show that there is a significant difference between year 1 students in rural and urban in term of communication skill, classification skill and observation skill. The findings from this study could contribute to the improvement of pedagogical practices in teaching Science in primary school.